2022
DOI: 10.3389/fpls.2022.1014631
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and yield responses of rotating planting strips and reducing nitrogen fertilizer application in maize–peanut intercropping in dry farming areas

Abstract: Improving cropping systems together with suitable agronomic management practices can maintain dry farming productivity and reduce water competition with low N inputs. The objective of the study was to determine the photosynthetic and yield responses of maize and peanut under six treatments: sole maize, sole peanut, maize–peanut intercropping, maize–peanut rotation–intercropping, 20% and 40% N reductions for maize in the maize–peanut rotation–intercropping. Maize–peanut intercropping had no land-use advantage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The potential activity of chloroplast PSII is reduced; the ability to convert light energy to chemical energy is impaired; the quantum transfer rate is decreased, and the amount of photophosphorylation is reduced, which may affect the assimilation of photosynthetic carbon in the host. Intercropping with maize and peanut ( Arachis hypogeae ) significantly increased the peanut Fv/Fm, qP, and ФPSII and decreased the NPQ compared with peanut monocropping [ 76 ]. The Fv/Fo, Fv/Fm, qP, and ФPSII and the absorption of nutrients were higher in the faba bean leaves grew under F. commune and cinnamic acid stress compared with faba bean monocropping, and the NPQ was lower in wheat -faba bean intercropping (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential activity of chloroplast PSII is reduced; the ability to convert light energy to chemical energy is impaired; the quantum transfer rate is decreased, and the amount of photophosphorylation is reduced, which may affect the assimilation of photosynthetic carbon in the host. Intercropping with maize and peanut ( Arachis hypogeae ) significantly increased the peanut Fv/Fm, qP, and ФPSII and decreased the NPQ compared with peanut monocropping [ 76 ]. The Fv/Fo, Fv/Fm, qP, and ФPSII and the absorption of nutrients were higher in the faba bean leaves grew under F. commune and cinnamic acid stress compared with faba bean monocropping, and the NPQ was lower in wheat -faba bean intercropping (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Mg plays a vital role in the activation of photosynthetic enzymes, such as Rubisco and FBPase [ 81 , 82 ]. Corn ( Zea mays ) and peanut intercropping significantly increased the activity and activation of Rubisco compared with peanut monocropping [ 76 ]. There were higher activities of Rubisco and RCA and Mg content when the wheat and faba bean were intercropped under F. commune and cinnamic acid stress compared with the monocropping of faba bean (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with sole peanut, Ci increased in the functional leaves of intercropped peanut, of which the smallest increase was observed in the M4P8 treatment. These results indicated that the decrease in photosynthetic capacity of intercropped peanut was caused by non-stomatal limitation (Gong et al, 2015;Yao et al, 2017;Han et al, 2022) and that the row ratio configuration of the M4P8 treatment was favorable to the interception and uptake of PAR by peanut leaves in the maize peanut intercropping system, thus improving the photosynthetic characteristics of the leaves.…”
Section: Intercropping Changes the Light Distribution And Photosynthe...mentioning
confidence: 95%
“…The limited expansion of arable land poses a significant impediment to the augmentation of total grain production in China, and enhancing the productivity per unit of land remains an ongoing challenge (Han et al, 2022). Intercropping can establish a stratified and distinct crop canopy structure above the ground, intercept more light energy, improve ventilation and light transmission conditions and take advantage of the side rows (Gong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%